Social science education students’ preparedness for problem-based hybrid learning - Saiful Amin; Sumarmi Sumarmi; Ravinesh Rohit Prasad (Journal of Education and Learning (EduLearn), 2023)
This research aims to investigate social science education students’ preparedness before they attend problem-based hybrid learning (PBHL). This research is quantitative research with an explorative survey method conducted on college students taking Social Science Education Program in Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia. The participant of this study were 118 students, subsisting of 32 male and 86 female students. This research used a questionnaire with a 1-4 Likert scale as an instrument to measure students’ readiness, weighted from their motivation, prospective behavior, and information and communication technolog (ICT) skills. The data collection process was carried out through Google Form in April 2020. This research used descriptive quantitative analysis to discover students’ preparedness and one-way ANOVA to identify the effect of gender type to the students’ preparation in PBHL. The results of this research show that social science education students’ preparedness (motivation, prospective behavior, and ICT skills) in PBHL is classified high, namely in the B+ category. Furthermore, the gender type has no significant effect on students’ preparedness for PBHL (p0.05). Recommendation based on the research result is the university has to facilitate easy internet access, such as by accelerating the bandwidth, internet connection, and promote other policies that support PBHL.